Sound-evoked tonic motility of cochlear outer hair cells in mice with stereociliary defects - James B. Dewey (Proceedings of the National Academy of Sciences, 2025)
Mammalian hearing sensitivity depends on the amplification of sound-induced cochlear vibrations by outer hair cells (OHCs). OHCs transduce deflections of their stereociliary bundles into receptor potentials that drive changes in cell length. While fast, phasic OHC length changes are thought to generate the forces that underlie cochlear amplification, OHCs also exhibit large tonic length changes in response to sound. These tonic length changes could theoretically arise from asymmetries in the mechanotransduction process that lead to tonic changes in membrane potential, though their exact origins and functional significance are uncertain. Here, in vivo cochlear vibration measurements reveal that sound can elicit tonic OHC motility in mice with stereociliary defects that eliminate cochlear amplification and presumably impair mechanotransduction. Tonic OHC motility in impaired mice was physiologically vulnerable but only weakly correlated with any residual phasic motility, suggesting a possible dissociation between the underlying mechanisms. Nevertheless, a simple model demonstrates how realistic changes to the OHC mechanotransducer function in impaired mice can lead to small but strongly asymmetric receptor potentials, producing sizable tonic length changes in the absence of any detectable phasic motility. Tonic OHC motility is therefore not a unique feature of sensitive ears and is the dominant active mechanical response in ears with certain types of deafness. Whether such tonic responses play a functional role in the normal or impaired cochlea remains to be determined.